Réponses

2014-05-03T12:30:07+02:00
DÉVELOPPER :
A = (2x - 3)(5 - x) - (2x - 3)²
A = 10x - 2x² - 15 + 3x - (4x² - 12x +9)
A = -2x² + 13x - 15 - 4x² + 12x - 9
A = -6x² + 25x - 24

FACTORISER :
A = (2x - 3)(5 - x) - (2x - 3)²
A = (2x - 3) [(5 - x) - (2x - 3)]
A = (2x - 3)(5 - x - 2x + 3)
A = (2x - 3)(-3x + 8)

Si x = -2, alors :
A = -6x² + 25x - 24
A = -6*(-2)² + 25*(-2) - 24
A = -24 - 50 - 24
A = -98

Si x = 3/2, alors
A = (2x - 3)(-3x + 8)
A = (2*3/2 - 3)(-3*3/2 + 8)
A = 0*(-3*3/2 + 8)
A = 0
2014-05-03T12:35:41+02:00
A=(2x.5-2x.x-3.5+3.x) - ((2x)^2 -2.2x.3+3^2)   
   =10x-2x^2-15+3x-4x^2+12x-9
   =-6x^2+25x-24
A=(2x-3)(5-x)-(2x-3)(2x-3)
   =(2x-3)[(5-x)-(2x-3)]
   =(2x-3)[5-x-2x+3]
   =(2x-3)(-3x+8)
x=-2⇒A=(-4-3)(6+8)=(-7)(14)=-98
x=3/2⇒A=(2.3/2-3)(-3.3/2+8)=0.(7/2)=0